FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE DECISION INVOLVEMENT GENERASI MILLENNIAL DI TRAVELOKA - Ryswaldi, Ridho; Pujani, Vera (Research Center and Case Clearing House PPM School of Management, 2020)
This research was conducted aiming to find out the factors that influence interests of millennial generation towards purchase decision involvement mediated by trust. The independent variable in this study is social media usage, eWOM, third party recognition, and legal framework. The sample collection technique is done by non probability sampling with purposive sampling. Millennial generation in this study has an age range of 18-34 years. Respondents are undergraduate and graduate students in the city of Padang. The number of respondents in this study were 216 respondents. The data analysis technique used in this study was Maximum Likelihood. In this study obtained social media usage, eWOM, and legal framework have a significant positive effect on purchase decision involvement, while third party recognition has no effect. For mediation by trusts, social media usage, eWOM, third party recognitiom, and legal framework, affect purchase decision involvementÂ